The magic of reality : how we know what's really true - Dawkins, Richard, 1941- (Free Press, 2011)
The author of "The God delusion" addresses key scientific questions previously explained by rich mythologies, from the evolution of the first humans and the life cycle of stars to the principles of a rainbow and the origins of the universe.